Identifikasi Potensi Pajak Penghasilan Atas Transaksi-Transaksi Bisnis Usaha Perbankan Syariah - Taufik Kurachman (Jurnal Pajak dan Bisnis, 2021)
The principle of sharia is the principle of Islamic law in economic activities based on fatwas issued by institutions that have the authority to determine fatwas in the field of sharia. Sharia-based activities include sharia banking, sharia insurance, sharia bonds or bonds (sukuk), sharia capital market instruments, sharia mutual funds, and other transaction activities that are based on sharia principles. To implement the provisions of article 31D of Law Number 36 Year 2008 concerning the Fourth Amendment to Law Number 7 of 1983 concerning Income Tax, the government needs to establish special regulations related to Income Tax on Sharia-Based Business activities. Activities in Sharia-Based Enterprises are carried out through several approaches including; profit sharing transactions in the form of mudharabah and musyarakah, sale and purchase transactions in the form of murabahah, salam, and isthisna, leasing transactions in the form of ijarah and ijarah muntahiya bittamlik; and lending and borrowing transactions in the form of qardh. The strengths of Islamic banking are the strong emotional emotional ties between share managers, banks and their customers, the existence of financing facilities that do not burden the customer from the start, the sharing system, and the application of profit sharing without interest. The disadvantages are too good assumptions that all customers are good, the revenue sharing system requirescomplex calculations, and mistakes in assessing projects to be financed by the bank with profit sharing. Provisions regarding income, expenses, and withholding tax or tax collection on sharia-based businesses based on PP 25 of 2009 apply mutatis mutandis provisions in the Income Tax Act. This means that in determining the taxation aspects of sharia-based business transactions, the provisions of the Taxation Law also apply, but with the necessary changes.